THE PROTOZOAN INOSITOL PHOSPHORYLCERAMIDE SYNTHASE: A NOVEL DRUG TARGET WHICH DEFINES A NEW CLASS OF SPHINGOLIPID SYNTHASE - Denny, Paul W. (2006)
Sphingolipids are ubiquitous and essential components of eukaryotic membranes, particularly the plasma membrane. The biosynthetic pathway for the formation of these lipid species is conserved up to the formation of sphinganine. However, a divergence is apparent in the synthesis of complex sphingolipids. In animal cells, ceramide is a substrate for sphingomyelin (SM) production via the enzyme SM synthase. In contrast, fungi utilise phytoceramide in the synthesis of inositol phosphorylceramide (IPC) catalysed by IPC synthase. Due to the absence of a mammalian equivalent, this essential enzyme represents an attractive target for anti-fungal compounds. In common with the fungi, the kinetoplastid protozoa (and higher plants) synthesize IPC rather than SM. However, orthologues of the gene believed to encode the fungal IPC synthase (AUR1) are not readily identified in the complete genome databases of these species. By utilising bioinformatic and functional genetic approaches, we have isolated a functional orthologue of AUR1 in the kinetoplastids, causative agents of a range of important human diseases. Expression of this gene in a mammalian cell line led to the synthesis of an IPC-like species strongly indicating that IPC synthase activity is reconstituted. Furthermore the gene product can be specifically inhibited by an anti-fungal targeting IPC synthase. We propose that the kinetoplastid AUR1 functional orthologue encodes an enzyme which defines a new class of protozoan sphingolipid synthase. The identification and characterisation of the protozoan IPC synthase, an enzyme with no mammalian equivalent, will raise the possibility of developing anti-protozoal drugs with minimal toxic side-affects.